Case Report on Presentation of Castleman’s Disease in a Patient with Mixed Connective Tissue Disorder - V, Ashwin Karuppan.; Ganesh, Deepika; P. S, Christina Jayaseely. (Indian Journal of Pharmacy Practice)
Castleman disease is also known as Angio follicular lymph node hyperplasia or giant lymph node hyperplasia. It is an uncommon benign B-cell lymphoproliferative condition which involves a hyperactive immune system. A 56-years-old female patient presented to the Emergency department with complaints of generalized tiredness, abdominal pain and fever for two weeks. She had a history of burning micturition, vomiting, black coloured stools and bilateral axilla pain. PET CT WHOLE BODY SCAN showed multiple enlarged hypermetabolic bilateral axillary and subpectoral lymph nodes with surrounding fat stranding. Left axillary lymph node excision biopsy was done under general anaesthesia and histopathology report showed both hyaline and plasmacytic variant of Castleman’s disease. The final diagnosis of mixed variant Castleman disease was made based on histological findings. MCTD is a rare autoimmune systemic disease whose features overlap with at least two connective tissue diseases like Rheumatoid Arthritis, Systemic Lupus Erythematosus and systemic sclerosis. With the patient’s diagnosis of MCTD considered, the patient was on steroid therapy (Prednisone 40 mg/day) to which the patient responded well. The individual did not develop any adverse effects and no symptoms developed despite the steroid therapy.
Keywords: Castleman’s disease; Mixed Connective Tissue Disorder; Mixed variant; Multicentric; Histopathology